Direct Photocoagulation Guided by Merged Retinal Images for the Treatment of Focal Diabetic Macular Edema. (12th March 2018) - Takamura, Yoshihiro; Matsumura, Takehiro; Arimura, Shogo; Gozawa, Makoto; Morioka, Masakazu; YutakaYamada; Inatani, Masaru
Abstract : Purpose . To introduce a novel laser photocoagulation (PC) protocol named merged image-guided PC (MIG-PC), which included merging the images of the fundus, optical coherence tomography (OCT) map, and fluorescein angiography (FA). We compared the anatomical and functional results between MIG-PC and FA-guided PC (FG-PC) for the treatment of focal diabetic macular edema (DME). Method . We examined the treatment outcomes in 27 consecutive eyes treated with MIG-PC compared with 28 matched eyes treated with FG-PC. We identified the microaneurysms (MAs) located in the focal edema areas and ablated them using focal PC. Best-corrected visual acuity (BCVA) and retinal thickness (RT) measured using OCT were compared between the groups at baseline and 2, 4, 8, 12, and 24 weeks after treatment. Results . The foveal and perifoveal RT were reduced after treatment in both the groups, and the perifoveal RT in the MIG-PC group was significantly lower than that in the FG-PC group at 4 weeks and thereafter. BCVA in the MIG-PC group was significantly higher than that in the FG-PC group at 12 and 24 weeks. The numbers of laser spots (p = 0.0001 ), additional laser treatments (p = 0.0121 ), and intravitreal injection of ranibizumab (p = 0.0012 ) in the MIG-PC group were significantly lower than those in the FG-PC group (Mann–Whitney test). Conclusion . MIG-PC contributed to the improvement in BCVA and reduction in RT, number of laser shots required, and retreatment rates. Based on our data, MIG-PC can be recommended for the treatment of focal DME. This trial is registered with IDUMIN000030390 .